Design and implementation of tactile auditory substitution system based on Gammatone filter - Jianguo Xing; Bing Xu; Ying Xue; Jixiang Zhu (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
Sensory substitution theory figures that all human sense could replace each other in some extent. This paper will try to use this theory to design a tactile auditory substitution system (TASS). TASS causes tactile sense by stimulating cutis with the use of electrode array. Gammatone filter bank of simulation cochlear basilar membrane collects features from speech signals, from which the stimulate information comes. Therefore, it opens up a new way to regain auditory information for the deaf. The result of the experiment shows that TASS is indeed a feasible solution for the deaf to obtain some simple speech information, which lays the foundation for the further study of obtaining more complex speech information for the deaf in the meanwhile.